Effect of Interprofessional Education (IPE) on Healthcare Students - Ismonah Ismonah; Ellyzabeth Sukmawati; Achmad Solechan; Di Huang (Yayasan Keluarga Guru Mandiri, 2026)
Interprofessional Education (IPE) is increasingly used to prepare healthcare students to work collaboratively in complex healthcare systems. However, evidence on its effectiveness in improving both collaborative attitudes and interprofessional competence remains inconsistent. This study examined the effect of IPE on students’ attitudes toward interprofessional collaboration and their interprofessional competence using a quantitative one-group pretest-posttestdesign. A total of 110 healthcare students participated in a structured IPE program that included collaborative case-based learning and interdisciplinary discussion. Data were collected using validated self-administered questionnaires before and after the intervention. Because the data were not normally distributed, the Wilcoxon signed-rank test was used for analysis. The findings showed a significant improvement in students’ attitudes after the IPE program (p 0.05). Interprofessional competence did not change significantly (p 0.05). These results indicate that short-term IPE may be more effective at developing positive attitudes than at building measurable competence. Longitudinal, practice-integrated IPE programs are therefore recommended to support sustainable competence development in.